Օժիտ (պատմական ակնարկ) - Մարիաննա Տիգրանյան (ՀՀ ԳԱԱ հրատ.)
Традиция выделять невесте приданое восходит к глубокой древности и это засвидетельствовано в документальных хрониках. Самый древний письменный источник – это кодекс правил вавилонского царя Хаммураппи – свидетельство того, что уже во II тысячелетии до н. э. в Тигрис-Евфратской долине юриспруденция изучала и рассматривала сложные, деликатные вопросы, касающиеся семьи и прав замужней женщины.This paper is a historical overview of dowry, an ancient custom. Numerous preserved records prove that it has been practiced for thousands of years. However, the oldest available record is the Code of king Hammrabi in ancient Babylon, which bears witness to the consideration of very complex and sensitive legal issues in the 2nd millennium BC in the Tigris-Euphrates river valley. Studies show that the dowry has at all times remained immune and never been considered as the property of the whole family.
Keywords: Ethnography; The family; Marriage; Woman; Manners and customs